Evolution and Synthesis of Carbon Dots: From Carbon Dots to Carbonized Polymer Dots - Xia, Chunlei; Zhu, Shoujun; Feng, Tanglue; Yang, Mingxi; Yang, Bai (Advanced science, 2019)
Despite the various synthesis methods to obtain carbon dots (CDs), the bottom‐up methods are still the most widely administrated route to afford large‐scale and low‐cost synthesis. However, as CDs are developed with increasing reports involved in producing many CDs, the structure and property features have changed enormously compared with the first generation of CDs, raising classification concerns. To this end, a new classification of CDs, named carbonized polymer dots (CPDs), is summarized according to the analysis of structure and property features. Here, CPDs are revealed as an emerging class of CDs with distinctive polymer/carbon hybrid structures and properties. Furthermore, deep insights into the effects of synthesis on the structure/property features of CDs are provided. Herein, the synthesis methods of CDs are also summarized in detail, and the effects of synthesis conditions of the bottom‐up methods in terms of the structures and properties of CPDs are discussed and analyzed comprehensively. Insights into formation process and nucleation mechanism of CPDs are also offered. Finally, a perspective of the future development of CDs is proposed with critical insights into facilitating their potential in various application fields. The classification of carbon dots (CDs) is improved and carbonized polymer dots (CPDs) are revealed with distinctive polymer/carbon hybrid structures and properties, as a new classification of CDs. The synthesis methods of CDs and effects of synthesis on the structures and properties of CPDs are discussed. Furthermore, insights are offered into the nucleation mechanism and the future development of CPDs.